2020
DOI: 10.1002/cssc.201902991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Li Confined Motion on NMR Quadrupolar Interactions: A Combined 7Li NMR and DFT‐MD Study of LiR2(PO4)3 (R=Ti or Zr) Phases

Abstract: Ab initio molecular dynamics (MD) simulations and NMR GIPAW (gauge including projector augmented wave) calculations have been used to analyze the coordination and mobility of Li ions in LiTi2(PO4)3 (rhombohedral), LiZr2(PO4)3 (triclinic), and LiZr2(PO4)3 (rhombohedral) phases. Significant discrepancies are observed between static calculations of 7Li quadrupolar parameters and experimental values. The dynamical origin of this disagreement is demonstrated by incorporating in the calculations thermal vibrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A similar experiment refers to the mobility of 7 Li ions in LiTi 2 (PO 4 ) 3 and LiZr 2 (PO 4 ) 3 [ 36 ]. A stimulus for this work was huge discrepancies between the results of a static NMR calculations and experimental data previously obtained for the above-mentioned systems.…”
Section: Summary Of the Chosen Studies Applying Both Aimd And Nmr Parameters Calculationmentioning
confidence: 99%
“…A similar experiment refers to the mobility of 7 Li ions in LiTi 2 (PO 4 ) 3 and LiZr 2 (PO 4 ) 3 [ 36 ]. A stimulus for this work was huge discrepancies between the results of a static NMR calculations and experimental data previously obtained for the above-mentioned systems.…”
Section: Summary Of the Chosen Studies Applying Both Aimd And Nmr Parameters Calculationmentioning
confidence: 99%
“…The decrease in C Q with increasing temperature is not a general behavior in crystalline solid electrolytes. Indeed, the opposite trend is observed in other crystalline solid electrolytes, such as LiTi 2 (PO 4 ) 3 , and Li-β-alumina. , Recent DFT–MD calculations have shown that framework vibrations and Li + -ion motion around the Li cavities lower the local symmetry around the Li + ions to increase C Q . In the case of LLTO, as the temperature increases, the TiO 6 tilt angle decreases and a phase transition to the cubic phases occurs. , These changes increase the local symmetry of the Li sites and consequently decrease C Q .…”
Section: Resultsmentioning
confidence: 99%
“…75,76 Recent DFT−MD calculations have shown that framework vibrations and Li + -ion motion around the Li cavities lower the local symmetry around the Li + ions to increase C Q . 77 In the case of LLTO, as the temperature increases, the TiO 6 tilt angle decreases 8 and a phase transition to the cubic phases occurs. 78,79 These changes increase the local symmetry of the Li sites and consequently decrease C Q .…”
mentioning
confidence: 99%
“…To deduce structural reasons that increase Li mobility, Density Functional Theory (DFT) and Molecular Dynamics (MD) simulations should be used. 28,29,38…”
Section: Pulse Eld Gradient Determinationsmentioning
confidence: 99%